Poverty Reduction and Growth Trust-Review of the Interest Rate Structure-Postponement. - International Monetary Fund. Finance Dept. (Washington, D.C. : International Monetary Fund, 2019)
This paper proposes to postpone the deadline for the next interest rate review by six months in light of the timing of the second stage of the Low-Income Countries (LIC) Facilities Review, and to maintain the zero percent interest rates applicable to ECF, SCF and ESF balances for this period.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Interest Rate Mechanism; Outstanding Balance; PP; PRGT Interest Rate Structure; Stand-By Credit Facility